Petrophysics for upscaling with applicability to assessment of enhanced oil recovery - Lipovetsky, Tatiana (2020)
This work presents methods for evaluating carbonate rock samples to obtain rock types and effective permeabilities in conformance with their corresponding representative elementary volumes to aid in the enhanced oil recovery (EOR) of oil reservoirs. Experimental data from petrophysical laboratory measurements were analyzed to characterize the formations and evaluation of upscaling techniques. The results integrate experimental routines, mathematical analyses, and computer simulations that provide information on porous media to support EOR operations in carbonate reservoirs, such as the Brazilian Pre-salt basins. This work evaluates the use of several petrophysical characterization techniques to improve rock typing and permeability estimation. The ultimate objective of the presented research was to enhance fluid recovery efforts, extendible to water-alternating-gas (WAG) injection technique, and other EOR applications for the Brazilian Pre-salt formations.